Effects of Calcium Ion, Calpains, and Calcium Channel Blockers on Retinitis Pigmentosa - Mitsuru Nakazawa (Journal of Ophthalmology)
Recent advances in molecular genetic studies have revealed many of the causative genes of retinitis pigmentosa (RP). These achievements have provided clues to the mechanisms of photoreceptor degeneration in RP. Apoptosis is known to be a final common pathway in RP and, therefore, a possible therapeutic target for photoreceptor rescue. However, apoptosis is not a single molecular cascade, but consists of many different reactions such as caspase-dependent and caspase-independent pathways commonly leading to DNA fractionation and cell death. The intracellular concentration of calcium ions is also known to increase in apoptosis. These findings suggest that calpains, one of the calcium-dependent proteinases, play some roles in the process of photoreceptor apoptosis and that calcium channel antagonists may potentially inhibit photoreceptor apoptosis. Herein, the effects of calpains and calcium channel antagonists on photoreceptor degeneration are reviewed.